Relationship Between Work Motivation and Affective Commitment in Kindergarten Teachers: Hubungan Antara Motivasi Kerja dengan Komitmen Afektif pada Guru Taman Kanak-Kanak - Suryatika, Friska Delta; Widyastuti, Widyastuti (Indonesian Journal of Innovation Studies, 2023)
High affective commitment will lead to attachment to duties and obligations as a teacher. In fact, there are still teachers who are less than optimal in delivering the material. The purpose of this study was to determine the relationship between teacher work motivation and affective commitment to Dharma Wanita Persatuan Kindergarten teachers in Candi Sidoarjo District. This research is a correlational quantitative research. The research population was 162 teachers, with a sample of 110 teachers using a simple random sampling technique. The data collection technique used the work motivation scale (α = 0.879) and the Affective Commitment scale (α = 0.942). The data analysis technique uses Pearson's product moment correlation with SPSS 17.0. The correlation coefficient value (rxy) = 0.185 with a significance of 0.009 <0.05, meaning that there is a significant positive relationship between Work Motivation and Affective Commitment to the Dharma Wanita Persatuan Kindergarten teachers in Candi Sidoarjo sub-district. The effect of work motivation on affective commitment in this study was 3.4%.